Electronic effect in intermetallic electrocatalysts with low susceptibility to CO poisoning during hydrogen oxidation - Bortoloti, F. [UNESP]; Garcia, A. C.; Angelo, A. C.D. [UNESP] (Elsevier, 2015)
This paper reports the results of Hydrogen Oxidation Reaction (HOR) experiments over ordered intermetallic (PtSn and PdSn) nanoparticles under CO-free and CO-covered surface conditions. The activity of PtSn toward the HOR was comparable to the activity of commercially available Pt/C. In addition, PtSn/C presented low susceptibility to CO poisoning. In the case of CO-covered surfaces, it was found that the CO was weakly adsorbed at the surface of the PtSn nanoparticles and it did not inhibit the HOR; in fact, this catalyst performed better than Pt/C under the same experimental conditions. X-Ray Absorption assays conducted in the present work proved that the ability of Sn to donate electrons to the Pt adsorption sites was crucial for the resulting intermetallic catalyst to display high activity in the HOR and low susceptibility to CO poisoning.
Keywords: CO poisoning; Electronic effect; Hydrogen oxidation reaction; Ordered intermetallic catalysts; PtSn